Why the public need a say in how patient data are Used for Covid-19 Responses - Aitken, Mhairi; Cunningham-Burley, Sarah; Darlington, Amy; Elstub, Stephen; Escobar, Oliver; Jones, Kerina; Sethi, Nayha; Thompson, Rachel (International Journal of Population Data Science, 2020)
The global coronavirus pandemic has clearly demonstrated the great urgency to collect and use patient data effectively to understand, track and manage the spread of Covid-19. The value of patient data in this pandemic is undeniable, however considerations around how - and by whom - such data should be collected, accessed and used, and for what purposes, remain to be fully debated and resolved. Who decides, and how such decisions are made remain unclear. We argue that public engagement and deliberation are essential for good governance and are key to establish and maintain a legitimate social licence for data practices around Covid-19.